Prevalence of Universal Medication Schedule prescribing and links to adherence. (24th January 2020) - Wolf, Michael S; Taitel, Michael S; Jiang, Jenny Z; Curtis, Laura M; Wismer, Guisselle A; Wallia, Amisha; Parker, Ruth M
Abstract: Purpose: A Universal Medication Schedule (UMS) that uses explicit language to describe when to take medicine has been proposed as a patient-centered prescribing and dispensing standard. Despite widespread support, evidence of its actual use and efficacy is limited. We investigated the prevalence of UMS instructions and whether their use was associated with higher rates of medication adherence. Methods: National pharmacy records were analyzed for a cohort of type 2 diabetic adults ≥18 years old (N = 676, 739) new to ≥1 oral diabetes medications between January and June 2014. Prescription instructions (N = 796, 909) dispensed with medications were classified as UMS or non-UMS. Instructions coded as UMS were further categorized as either providing precise UMS language (tier 1: "take 1 pill at morning, noon, evening, or bedtime") or offering some explicit guidance (tier 2: "take 1 tablet by mouth before breakfast"; tier 3: "take 1 tablet twice daily with a meal"). Adherence over 12 months was measured by proportion of days covered. Results: One-third of instructions (32.4%, n = 258, 508) were classified as UMS (tier 1: 12.6%, n = 100, 589; tier 2: 6.0%, n = 47, 914; tier 3: 13.8%, n = 110, 005). In multivariable analyses, UMS instructions (all tiers) exhibited better adherence compared to non-UMS instructions (relative risk [RR], 1.01; 95% confidence interval [CI], 1.00-1.02; P = 0.01). Patients older than 65 years who were less educated and taking medication more than once daily received greater benefit from tier 1 UMS instructions (RR, 1.14; 95% CI, 1.07-1.21; P < 0.001). Conclusion: While infrequently used, the UMS could help older, less-educated patients adhere to more complex regimens with minimal investment.